Maturity related changes in inter-subject variability during cutting manoeuvres of adolescent soccer players - Dupré, T.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2019)
The incidence of various injury rises with the onset of puberty and the growth spurt around 13 years. The biomechanical reasons are unclear. Therefore, the purpose of this study was to investigate the kinematics of the hip and knee joint of pre peak height velocity (PHV) and mid PHV soccer players during a 90° cutting manoeuvre. Twenty-two participants were investigated with a 3D movement analysis system and a force platform. Results showed no statistical difference in the time series of the hip and knee joint kinematics. Average variability of the knee flexion and internal rotation angle were significantly higher for the pre PHV group. This indicates a consolidation of the movement technique during the phase of the growth spurt, caused by the fast changes in length and masses of the segments.